Participation et gestion dans les parcs nationaux de montagne : approches anglo-saxonnes - Stéphane Héritier (Revue de Géographie Alpine)
Public involvement has become a key concept in conservation management worldwide. This paper intends to give an overview on four countries known to have established national parks for over a century, and often in clearing the land from previous ‘indigenous’ or local occupation. Since the seventies, public participation has become a common practice in parks’ management, even if reality does not fit always perfectly with theory. The paper analyses general trends of public participation in parks management practices, which are most often considered as a successful governance policies by most authors, and is also considered as a way to build participative democracy. The analysis using the level of scale intends to show that public participation can also fragment the stakeholders, making really difficult the emergence of any efficient coalition of stakeholders.